RETRACTED: Videogames and problems of media translation in the context of comparison of narratology and ludology - Kluev Artem; Marinina Julia; Natalia Shmeleva; Aksenova Marina; Merzlyakova Anna (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001